2014
DOI: 10.1186/1471-2180-14-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two transketolases encoded on the chromosome and the plasmid pBM19 of the facultative ribulose monophosphate cycle methylotroph Bacillus methanolicus

Abstract: BackgroundTransketolase (TKT) is a key enzyme of the pentose phosphate pathway (PPP), the Calvin cycle and the ribulose monophosphate (RuMP) cycle. Bacillus methanolicus is a facultative RuMP pathway methylotroph. B. methanolicus MGA3 harbors two genes putatively coding for TKTs; one located on the chromosome (tkt C ) and one located on the natural occurring plasmid pBM19 (tkt P ).ResultsBoth enzymes were produced in recombinant Escherichia coli, purified and shown to share similar biochemical parameters in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…B. methanolicus MGA3 Mdh and Mdh2 activities were previously shown to be increased by Act under alkaline pH conditions [5]. However, because neutral intracellular pH can be assumed for B. methanolicus [18,19], we decided to additionally study the enzymes at pH 7.4 to represent more physiological conditions. The enzyme activities of Mdh and Mdh2 were determined using methanol as a substrate at pH 9.0 and pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
“…B. methanolicus MGA3 Mdh and Mdh2 activities were previously shown to be increased by Act under alkaline pH conditions [5]. However, because neutral intracellular pH can be assumed for B. methanolicus [18,19], we decided to additionally study the enzymes at pH 7.4 to represent more physiological conditions. The enzyme activities of Mdh and Mdh2 were determined using methanol as a substrate at pH 9.0 and pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
“…Second, several studies have compared the activities of both the plasmid and chromosomal RuMP-pathway regeneration genes and found that they possess somewhat different activities [24][25][26]. For example, the chromosomally encoded fructose 1,6 bisphosphatase had higher activity and a lower K m for fructose 1,6-bisphosphate compared with the plasmid-encoded copy.…”
Section: Hcho Assimilation Via the Rump Pathwaymentioning
confidence: 97%
“…5C). In other species for which transketolase kinetic constants have been determined, k cat values can be similar to 10-fold lower, as is the case with Saccharomyces cerevisiae, or more than 3 orders of magnitude lower, as in Bacillus methanolicus (42,43). These observations raise questions about the minimal level of transketolase activity required for growth and why WT S. Typhimurium utilizes three transketolase isoenzymes that exhibit high levels of transketolase activity.…”
Section: Discussionmentioning
confidence: 99%